x=.05x(x+y)

Simple and best practice solution for x=.05x(x+y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x=.05x(x+y) equation:


Simplifying
x = 0.05x(x + y)
x = (x * 0.05x + y * 0.05x)

Reorder the terms:
x = (0.05xy + 0.05x2)
x = (0.05xy + 0.05x2)

Solving
x = 0.05xy + 0.05x2

Solving for variable 'x'.

Reorder the terms:
x + -0.05xy + -0.05x2 = 0.05xy + -0.05xy + 0.05x2 + -0.05x2

Combine like terms: 0.05xy + -0.05xy = 0.00
x + -0.05xy + -0.05x2 = 0.00 + 0.05x2 + -0.05x2
x + -0.05xy + -0.05x2 = 0.05x2 + -0.05x2

Combine like terms: 0.05x2 + -0.05x2 = 0.00
x + -0.05xy + -0.05x2 = 0.00

Factor out the Greatest Common Factor (GCF), 'x'.
x(1 + -0.05y + -0.05x) = 0.00

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(1 + -0.05y + -0.05x)' equal to zero and attempt to solve: Simplifying 1 + -0.05y + -0.05x = 0 Reorder the terms: 1 + -0.05x + -0.05y = 0 Solving 1 + -0.05x + -0.05y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -0.05x + -1 + -0.05y = 0 + -1 Reorder the terms: 1 + -1 + -0.05x + -0.05y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -0.05x + -0.05y = 0 + -1 -0.05x + -0.05y = 0 + -1 Combine like terms: 0 + -1 = -1 -0.05x + -0.05y = -1 Add '0.05y' to each side of the equation. -0.05x + -0.05y + 0.05y = -1 + 0.05y Combine like terms: -0.05y + 0.05y = 0.00 -0.05x + 0.00 = -1 + 0.05y -0.05x = -1 + 0.05y Divide each side by '-0.05'. x = 20 + -1y Simplifying x = 20 + -1y

Solution

x = {0, 20 + -1y}

See similar equations:

| 16+4x=28 | | -x/20-2=16 | | 5x=3x+1500 | | 3t^2-4t+7t=(t-2) | | 3z^2+5=0 | | 3y-5=3y-18 | | sqrt(x+2)+sqrt(2-4x)=sqrt(10) | | 18/(4x(11-6)-11) | | E^6x+79=36 | | 3c-5+2c+8= | | 5x-4=4x+1 | | (X^2)/200/X | | 5x(5-3)25= | | sqrt(x^2-16)=3 | | -5x+4=-2-3x | | 42=2/3v | | sqrt(x^2-16)+sqrt(x^2-9)=7 | | 3-9h-2+7h= | | 12-4x=10-1,5x | | 4x^4-17x^2-50=0 | | 12-4x=8-1,5x | | 3(5g-7)-8= | | X-.15=510 | | 7-4x=2-1,5x | | -7(z+4)=3-6z | | -1-5x=-x-1 | | 312-76=278 | | -30=976+9 | | p=174-(-800) | | r=-2+(-56)+(786)+(-97) | | 3(5x+4)=4(x-8) | | e=79+(-31)+(-140) |

Equations solver categories